2005
DOI: 10.1530/rep.1.00541
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoal competition in common carp (Cyprinus carpio): what is the primary determinant of competition success?

Abstract: The percentage of sperm motility (92-100%), spermatozoan velocity (112 -163 mm·s 21 ) and control hatching rates (83-96%) were evaluated for each of six gold and five green male common carp (Cyprinus carpio). In all 30 possible paired combinations of sperm-competition tests, hatching rates of 90 -97% were achieved. The mean percentage of offspring sired was strongly influenced by the male used (P < 0.001, R 2 5 0.91). The best male sired an average of 88% of the offspring in its competition tests, and the wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…Theoretically, the probability of a sperm encountering an egg is a function of sperm swimming speed, gamete concentration and egg target area (Levitan 2000, Riffell & Zimmer 2007. Sperm density (spermatocrit) has been shown to positively influence male reproductive success in a number of teleost species, including cod (Rakitin et al 1999b), bluegill Lepomis macrochirus (Stoltz & Neff 2006) and common carp Cyprinus carpio (Linhart et al 2005). Wild males had a higher VCL both early and late in their spawning period, and had significantly higher spermatocrit values early and a tendency towards higher values late in their spawning period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the probability of a sperm encountering an egg is a function of sperm swimming speed, gamete concentration and egg target area (Levitan 2000, Riffell & Zimmer 2007. Sperm density (spermatocrit) has been shown to positively influence male reproductive success in a number of teleost species, including cod (Rakitin et al 1999b), bluegill Lepomis macrochirus (Stoltz & Neff 2006) and common carp Cyprinus carpio (Linhart et al 2005). Wild males had a higher VCL both early and late in their spawning period, and had significantly higher spermatocrit values early and a tendency towards higher values late in their spawning period (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This link between sperm viability and male sexual ornamentation in guppies may explain why paternity is biased towards highly ornamented males when the number of sperm from competing males is held constant (Evans et al 2003). Other measures of sperm quality, including sperm mobility (ability to penetrate an inert medium), have been implicated in meditating paternity success in chickens (Birkhead et al 1999), while sperm swimming speeds (Gage et al 2004) and the percentage of motile sperm (Linhart et al 2005) are known to regulate competitive fertilization success in externally fertilizing fishes. Among rodents, sperm competition intensity covaries positively with the ability of sperm to become capacitated and undergo the acrosome reaction, both of which are important prerequisites to fertilization .…”
Section: Sperm Phenotypementioning
confidence: 99%
“…Studies of individual species have also reported a positive relationship between sperm swimming speed and ejaculate competitiveness (e.g. Birkhead et al ., ; Gage et al ., ; Linhart et al ., ; Pizzari et al ., ; Gasparini et al ., 2010 b ; Boschetto, Gasparini & Pilastro, ; Beausoleil et al ., ; but see Dziminski et al ., ; Smith, ). By extension, it is assumed that faster swimming sperm will elevate fertility because this increases the likelihood of sperm reaching eggs before they die.…”
Section: Introductionmentioning
confidence: 98%